2019
DOI: 10.3847/1538-4357/ab4516
|View full text |Cite
|
Sign up to set email alerts
|

Determining Fireball Fates Using the α–β Criterion

Abstract: As fireball networks grow, the number of events observed becomes unfeasible to manage by manual efforts. Reducing and analysing big data requires automated data pipelines. Triangulation of a fireball trajectory can swiftly provide information on positions and, with timing information, velocities. However, extending this pipeline to determine the terminal mass estimate of a meteoroid is a complex next step. Established methods typically require assumptions to be made of the physical meteoroid characteristics (s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 32 publications
(51 reference statements)
0
49
0
Order By: Relevance
“…2012; Sansom et al. 2019a). The dimensionless ballistic (α) and mass loss (β) parameters calculated for this fireball are α = 8.34 and β = 1.063 (Fig.…”
Section: Trajectory Modelingmentioning
confidence: 99%
“…2012; Sansom et al. 2019a). The dimensionless ballistic (α) and mass loss (β) parameters calculated for this fireball are α = 8.34 and β = 1.063 (Fig.…”
Section: Trajectory Modelingmentioning
confidence: 99%
“…Finally, the values of α or β can be also retrieved accurately under certain meteoroid atmospheric fragmentation scenarios (see Gritsevich 2008a;Moreno-Ibáñez 2018). It has been demonstrated that these parameters can be used to identify meteorite-producing fireballs as well as to predict formation of impact craters for larger impactors (Gritsevich et al 2012;Turchak & Gritsevich 2014;Sansom et al 2019). On one hand, this allows for the new criterion to be used for meteoritedroppers (and not only to disintegrating fireballs); and on the other hand, it provides a reliable classification for the atmospheric behaviour of meter-sized projectiles.…”
Section: Figure 2 -Diagram Showing the Lnα And Lnβ For Morp And Pn Damentioning
confidence: 99%
“…The suitability to use the parameters α and β to classify meteoroid impacts was introduced by Gritsevich, Stulov & Turchak (2009, 2012 and was recently demonstrated on a large observational dataset by Sansom et al (2019). In particular, using this approach Sansom et al (2019) identify meteorite-producing fireballs illustrating their 'clustering' on the α-β plot. It was suggested in Moreno-Ibáñez, Gritsevich & Trigo-Rodríguez (2015, 2017, as a prospect for future research, that the mathematical combination of α and β could also lead to the revision of the PE criterion.…”
Section: Introductionmentioning
confidence: 99%
“…We then apply our numerical model to the Chelyabinsk superbolide in order to study its dynamical behavior. For the sake of simplicity, our model considers a constant ablation coefficient and the shape factor, even though these parameters could vary in different ablation stages [33][34][35].…”
Section: Introductionmentioning
confidence: 99%